ANALISIS IMPLEMENTASI TEKNIS RELIABILITY, AVAILABILITY, MAINTAINABILITY AND SAFETY (RAMS) PADA RESOR JALAN REL BERDASARKAN SNI IEC 62278-2002 BIDANG PERKERETAAPIAN DI STASIUN PURWAKARTA - Rikzan Bachrul Ulum; Agung Widarman; Almaida Nuriz Mayumi; Hendi Iskandar (LPPM Sekolah Tinggi Teknologi Nusantara Lampung, 2024)
PT KAI is a land transport service company. The number of people who switch to this mode of transport makes PT KAI make efforts in improving services to maintain public trust in order to continue to choose train services as the main land transport. Purwakarta Station is a station within the Bandung 2 operating area that serves local and long-distance train travel. Purwakarta Station has a single line from Purwakarta to Ciganea and a doublie line between Purwakarta to Cibungur. To improve the performance and quality of the railway and continuous innovation in its maintenance, in this case RAMS as a performance indicator in a maintenance management and railway service indicator. RBD is used to analyse the reliabilitu and availability of a system, FTA is used to identify the factors that cause damage to arise. FMEA is used to determine and evaluate potential failures and identify which maintenance actions need to be taken to reduce the chamce of failure and also increse safety in the railway environment.